Lactose intolerance and cow's milk protein allergy (CMPA): the main clinical considerations (Research, Society and Development, 2022)
Objective: To describe, through the scientific literature in a narrative way, the main clinical considerations on the subject of lactose intolerance and cow's milk protein allergy (CMPA) in pediatrics. Methodology: This is a narrative review of literature based on the platforms of SciELO, PubMed, Brazilian Journal of Health Review, Acervo Mais Index Base, Research, Society and Development and other renowned literature on the subject. Results and Discussion: Lactose intolerance (IL) and Cow's Milk Protein Allergy (ALPV) are erroneously equated, but both are distinct diseases. Lactose intolerance is a phenomenon in which lactase is not properly digested, and through bacterial action results in the characteristic discomfort of the condition, but does not characterize an allergic reaction. In contrast, milk allergies focus on the protein, which exceeds the intestinal mucosal barrier and reaches the bloodstream. This results in digestive appearances such as mushy diarrhea, bloody stools, weight gain deficit, and systemic eruptions such as urticaria, eczema, and even anaphylactic shock. The organ dysfunctions are different and in this study the main most significant points for the pediatric clinic were highlighted in a descriptive way. Conclusions: In view of the collection of information, it can be clarified that food allergy and intolerance is a relevant topic in pediatrics, as it can be associated with significant morbidity, with a negative impact on the child's survival and quality of life, if not properly treated.